Vision-based production of personalized video - Chatzis, Sotirios P.; Kosmopoulos, Dimitrios I.; Doulamis, Anastasios D.; Makris, Alexandros; Doulamis, Nikolaos D.; Middleton, Stuart E. (My University, 2009)
In this paper we present a novel vision-based system for the automated production of personalized video souvenirs for visitors in leisure and cultural heritage venues. Visitors are visually identified and tracked through a camera network. The system produces a personalized DVD souvenir at the end of a visitor's stay allowing visitors to relive their experiences. We analyze how we identify visitors by fusing facial and body features, how we track visitors, how the tracker recovers from failures due to occlusions, as well as how we annotate and compile the final product. Our experiments demonstrate the feasibility of the proposed approach
Keywords: Signal processing; Automation; Computer science